Studi Kasus Hubungan Antara Aktivitas Fisik Dan Kebiasaan Sarapan Dengan Prestasi Belajar Pada Siswa - Pomalingo, Anna Y; Mokodompis, Yasir; Amrain, Muhammad Zul Fadhoo’il (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
Physical activity and breakfast habits can affect a person's physiological condition and children's learning concentration at school. The formulation of the problem is to determine the relationship between physical activity breakfast habits and learning achievement. This study aims to determine the relationship between physical activity and breakfast habits and learning achievement in students (case study at State Elementary School 23 Dungingi, Gorontalo City). This research used quantitative research with a cross-sectional study design. The population in this study amounted to 42 students. The sampling technique was selected using total sampling. Data collection using a questionnaire. Data analysis used in this study was univariate analysis and bivariate analysis with a chi-square statistical test. The results showed light physical activity (73.8%) and moderate physical activity (26.2%), breakfast habits (71.4%), and not breakfast habits (28.6%), good learning achievement (47.6%), and poor learning achievement (52.4%). Physical activity with learning achievement (p-value =0.003 < α = 0.05) and breakfast habits with learning achievement (p-value =0.000 < α = 0.05) There is a relationship between physical activity and breakfast habits with learning achievement. Students are expected to get used to breakfast and pay more attention to the food consumed and regular physical activity.